2008
DOI: 10.1177/0961203307085246
|View full text |Cite
|
Sign up to set email alerts
|

Striking alteration of some populations of T/B cells in systemic lupus erythematosus: relationship to expression of CD62L or some chemokine receptors

Abstract: Recent studies have revealed new populations of T/B cells, including central/effector memory, follicular T cells and CXCR3+ or CXCR4+ B cells. In the present study, changes in these populations of CD4+ T cells were examined on the basis of the expression of CD62L, CCR7 and CXCR5 in patients with systemic lupus erythematosus (SLE) in relation to CCL21 and CXCL10. Changes in CXCR3+, CXCR4+ and CXCR5+ B cells were also examined. CD62L and various chemokine receptors were examined by flow cytometry analysis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…3A and B). [38,39]. We also found that the memory/activated cells were skewed toward the CD25 NEG compartment in SLE patients compared to normal donors ( Fig.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…3A and B). [38,39]. We also found that the memory/activated cells were skewed toward the CD25 NEG compartment in SLE patients compared to normal donors ( Fig.…”
supporting
confidence: 55%
“…Previous studies have shown that granzyme B is regulated in part by EOMES, while CD319 has activating properties on NKT cells, but little information regarding these two proteins is available for human CD4 + T cells [35][36][37]. [38,39]. We also found that the memory/activated cells were skewed toward the CD25 NEG compartment in SLE patients compared to normal donors ( Fig.…”
Section: Cd25mentioning
confidence: 56%
“…Henneken and colleagues noticed that contrary to RA patients, very few circulating (memory) B cells from lupus patients express high levels of CXCR3 25 . However a recent paper mentions an increase in the ratio of CXCR3 + B cells together with an increase in CXCL10 serum levels in patients with SLE 26 . These apparently contradictory results may be due to differences in flow cytometry analyses or to different clinical characteristics of the selected patients.…”
Section: Contribution Of Cxcr3 and Cxcr3‐binding Chemokines To The Pamentioning
confidence: 98%
“…25 However a recent paper mentions an increase in the ratio of CXCR3 + B cells together with an increase in CXCL10 serum levels in patients with SLE. 26 These apparently contradictory results may be due to differences in flow cytometry analyses or to different clinical characteristics of the selected patients. Finally, very interesting information came out from a recent paper by Nicholas and colleagues, who showed that, in some SLE patients, a population of circulating memory B cells, expressing high levels of CD19, is enriched in autoreactivity (anti-Smith antigen B cells) and specifically expresses elevated CXCR3 levels.…”
Section: Cxcr3 In Slementioning
confidence: 99%
“…Considering the high number of Treg cells in the ATLO, we could speculate that FoxP3-expressing T cells could be precursors of Tfh cells, directly in situ, in the diseased arteries. Moreover, Tfh cells can be found in the blood of patients with SLE and Sjogren's syndrome [146,147], suggesting that, given the rising incidence of accelerated atherosclerosis in patients with SLE [131], the circulating Tfh compartment may play a role in vascular pathology too.…”
Section: Tfh Cells In Vascular Pathologymentioning
confidence: 99%